2023
DOI: 10.3171/2023.1.peds22312
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clinical model to predict vagus nerve stimulation response in pediatric patients with drug-resistant epilepsy

Abstract: OBJECTIVE Epilepsy impacts 470,000 children in the United States. For patients with drug-resistant epilepsy (DRE) and unresectable seizure foci, vagus nerve stimulation (VNS) is a treatment option. Predicting response to VNS has been historically challenging. The objective of this study was to create a clinical VNS prediction tool for use in an outpatient setting. METHODS The authors performed an 11-year retrospective cohort analysis with 1-year follow-up. Patients < 21 years of age with DRE who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Patients with generalized seizures achieving a > 50% reduction in seizure frequency 1 and 2 years after VNS implantation were 46 and 49%, respectively. On the other hands, focal seizures are more likely to respond to VNS than generalized seizure ( 24 ). Although it is still controversial which type of seizure VNS is effective for, involvement of the thalamus in seizure onset suggests a mechanism for the effect of VNS on generalized seizure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with generalized seizures achieving a > 50% reduction in seizure frequency 1 and 2 years after VNS implantation were 46 and 49%, respectively. On the other hands, focal seizures are more likely to respond to VNS than generalized seizure ( 24 ). Although it is still controversial which type of seizure VNS is effective for, involvement of the thalamus in seizure onset suggests a mechanism for the effect of VNS on generalized seizure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited research on the prognostic factors of VNS in children, and the selection of surgical methods mainly relies on the clinical experience of doctors, lacking clear surgical indicators. Nallammai Muthiah found that < 4-year epilepsy duration before VNS and focal motor seizures were factors associated with VNS response ( 9 ), yet no correlation was found between epilepsy duration and VNS response in J Janszky's research ( 10 ). Due to sample heterogeneity, there is no uniform conclusion on predictors of VNS efficacy, and there is still a lack of simple predictive models to predict VNS efficacy in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Years of clinical trials have confirmed its safety, and it has been approved for use in the treatment of DRE in children since 1997 (7). Studies have shown that VNS can reduce seizures to a certain degree in epileptic children, and improve cognition, memory, emotion, and other functions (8). However, there is limited research on the prognostic factors of VNS in children, and the selection of surgical methods mainly relies on the clinical experience of doctors, lacking clear surgical indicators.…”
Section: Introductionmentioning
confidence: 99%